2010
DOI: 10.4018/jsse.2010070105
|View full text |Cite
|
Sign up to set email alerts
|

Agile Software Development

Abstract: In this article, the authors contrast the results of a series of interviews with agile software development organizations with a case study of a distributed agile development effort, focusing on how information security is taken care of in an agile context. The interviews indicate that small and medium-sized agile software development organizations do not use any particular methodology to achieve security goals, even when their software is web-facing and potential targets of attack. This case study confirms th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Consistent with the Errata survey, Nicolaysen et al [9] found that very few of the companies were utilizing methodologies for creating secure software. The developers had no formal training in developing secure software and very few were concerned about security.…”
Section: A Software Security In Norwegian Organizationsmentioning
confidence: 87%
See 1 more Smart Citation
“…Consistent with the Errata survey, Nicolaysen et al [9] found that very few of the companies were utilizing methodologies for creating secure software. The developers had no formal training in developing secure software and very few were concerned about security.…”
Section: A Software Security In Norwegian Organizationsmentioning
confidence: 87%
“…Two studies have recently been conducted to determine the state of practice in Norwegian organizations with regard to security. Nicolaysen et al [9] studied the software security initiatives of six companies using agile software development methodologies and Jaatun et al [10] studied 20 public Norwegian organizations developing software.…”
Section: A Software Security In Norwegian Organizationsmentioning
confidence: 99%
“…d) ASD teams can assist customers in recognizing the importance and value of QRs, since customers in some domains may overlook important QRs or may not have adequate knowledge about QRs [40]. For instance, customers in the energy domain may overlook important QRs such as security [41]. Related Work: [5], [6], [8], [10], [30], [38]- [41] 2) RECOGNIZE THE NEED FOR OPTIMAL DOCUMENTATION OF QRs Description: Agile teams should acknowledge the need for optimal documentation of QRs (i.e., a satisfactory level of QR documentation that will not compromise agility and product quality).…”
Section: ) Recognize the Significance Of Qrsmentioning
confidence: 99%
“…For instance, customers in the energy domain may overlook important QRs such as security [41]. Related Work: [5], [6], [8], [10], [30], [38]- [41] 2) RECOGNIZE THE NEED FOR OPTIMAL DOCUMENTATION OF QRs Description: Agile teams should acknowledge the need for optimal documentation of QRs (i.e., a satisfactory level of QR documentation that will not compromise agility and product quality). They should take actions to meet the need for optimal documentation of QRs and start documenting QRs at early stages.…”
Section: ) Recognize the Significance Of Qrsmentioning
confidence: 99%
See 1 more Smart Citation